PERAN TUHA PEUT DALAM PERLINDUNGAN ANAK YANG BERHADAPAN DENGAN HUKUM DI ACEH BESAR - Mansari, Mansari (Department of Anthropology, 2018)
Reusam which usually regulates public behavior about habits undertaken by the public in an unwritten form, is now beginning to be written in written form. The formation of gampong reusam was formed by Tuha Peut Gampong which was discussed together with the keuchik and community leaders of the gampong. This research aims to find out how the process of reusam formation of child protection in Aceh Besar and how the role of tuha peut in determining the direction of development of child protection reusam in Aceh Besar. This research uses qualitative research with data source from primary data obtained through interview with Keuchik, Tuha Peut Gampong and Female Woman. The results showed Tuha Peut has an important role in the development of a gampong reusam that adopts local and applicable local values in Aceh. These values are deliberation, mediation and the use of adat sanctions for child offenders in cases that occur, such as Advice, Warning, apology, fines, compensation, returned to the family, Establishment of Child Protection Committees dealing with law and engagement government agencies.